El hombre de Cuchipuy ( prehistoria de Chile central) - Kaltwasser, Jorge; Medina, Alberto; Munizaga, Juan (Revista Chilena de Humanidades, 2015)
These three investigators summarize the most relevant consequences deriving from the discovery of a pre-Hispanic cemetery in the region called Cuchipuy, near the town of San Vicente de Taguatagua, in the central part of Chile. This burying-place has four levels, the oldest of which is dated c. 8.000 year ago on the basis of radiocarbon analyses. The findings constitute a major contribution to studies on the biological variability of American man, giving support to hypotheses suggesting arrival during different periods. Thus, the Cuchipuy Cemetery, together with Indian Knoll, and Guayas, in Ecuador, because of its antiquity, extension and number of burials, occupies a relevant position within the studies on the Archaic period in America.